Remembering in conversations the social sharing and reshaping of memories. [article]. - Hirst, William
People constantly talk about past experiences. Burgeoning psychological research has examined the role of communication in remembering by placing rememberer in conversational settings. In reviewing this work, we first discuss the benefits of collaborative remembering (trans-active memory and collaboratie facilitation) and its costs (collaborative inhibition, information sampling biases, and audience tuning). We next examine how conversational remembering affects subsequent memory. Here , we address influences on listeners' memory through social contagion, resistance to such influences, and then retrieval/reexposure effects on either speaker or listener, with a focus o retrieval-induced forgetting. Extending the perspective beyond single interactions, we consider work that has explored how the above effects can spread across networks of several individuals. We also explore how a speaker's motive to form a shared reality with listeners can moderate conversational effects on memory. Finally, we discuss how these various conversational effects may promote the formation of collective memories.- (from the authors)